O enlaçamento enunciativo de um ritual carnavalizado : cenografia e ethos discursivo em sambas-enredo de escolas carnavalescas do Meio-Oeste catarinense - Facin, Débora (2012)
This research, entitled The enunciative bonding of a carnivalized ritual: scenography and discursive ethos in plots of samba schools from the Midwest of Santa Catarina, aims to analyze the scenography and the discursive ethos inferred from the carnivalized language enrolled in plots of samba schools from Joaçaba and Herval d'Oeste, Santa Catarina, through the concepts of Bakhtin (1965/2010a) on carnivalization, and Maingueneau (1984/2008a, 1987/1997, 2005/2008b, 2006/2008c, 2000/2011a , 2011b) in relation to scenography and discursive ethos. A study of this nature is justified by the fact that the carnivalization of Bakhtin can be analyzed in texts of any time, and especially from the theoretical and methodological proposal of Maingueneau (1984/2008a), it is possible to investigate every speech paying attention to the plans that constitute it. It is through the plans that consolidate the global semantics and, as a consequence of this, the scenography and the discursive ethos, that the carnivalized brands in samba plots are analyzed. That's because the studies of Maingueneau allow an orientation, as we understand, more precise in terms of methodology and analysis procedures. For us, there is need to investigate the effects of the language in carnival samba plots, but under the guidance of a frame that gives us some theoretical categories of analysis that could be verified in the materiality of the text, marked by linguistic clues in the speech. The procedures adopted characterize this research as descriptive, bibliographic, with qualitative approach. To better structure it, as well to describe the operation of the discursive plans, we approach the semantic model proposed by Maingueneau (1984/2008a) to the evidential paradigm of Ginzburg (1989), once Maingueneau refutes the idea of an absolute position, of a generalizing and totalizing look as discursive analyzes, the linguist makes clear his microscopic vision on all plans that makes one given discourse. It is understood, therefore, the plans that constitute the global semantics as some signs that subsequently allow referencing the scenography and the ethos of a speech as categories that are inferred from the hypothesis of global semantics